Plant glandular trichomes mediate protective mutualism in a spider-plant system - Morais-Filho, José Cesar [UNESP]; Romero, Gustavo Q. [UNESP] (Wiley-Blackwell, 2010)
1. Although several species of Peucetia (Oxyopidae) live strictly in association with plants bearing glandular trichomes worldwide, to date little is known about whether these associations are mutualistic.2. In this study we manipulated the presence of Peucetia flava on the glandular plant Rhynchanthera dichotoma in the rainy and post-rain season, to test the strength of its effects on leaf, bud, and flower damage and plant reproductive output. In addition, we ran independent field experiments to examine whether these sticky structures improve spider fidelity to plants.3. Peucetia suppressed some species of foliar phytophages, but not others. Although spiders have reduced levels of leaf herbivory, this phenomenon was temporally conditional, i.e. occurred only in the post-rain but not in the rainy season. Floral herbivory was also reduced in the presence of spiders, but these predators did not affect plant fitness components.4. Plants that had their glandular trichomes removed retained fewer insects than those bearing such structures. Spiders remained longer on plants with glandular trichomes than on plants in which these structures had been removed. Isotopic analyses showed that spiders that fed on live and dead labelled flies adhered to the glandular hairs in similar proportions.5. Spiders incurred no costs to the plants, but can potentially increase individual plant fitness by reducing damage to reproductive tissues. Temporal conditionality probably occurred because plant productivity exceeded herbivore consumption, thus dampening top-down effects. Specialisation to live on glandular plants may have favoured scavenging behaviour in Peucetia, possibly an adaptation to periods of food scarcity.
Keywords: Conditional outcomes; food web; glandular trichomes; host fidelity; Melastomataceae; Neotropical region; Peucetia; protective mutualism; spider-plant interaction; swamp; top-down and bottom-up forces